Computerized Tomography-Based Volumetric Analysis Of The Maxillary, Sphenoid, And Frontal Sinuses: An Observational Study - Ashish Dhakal; Bikash Lal Shrestha; Monika Pokharel; Samip Shrestha; Subindra Karki; Krishna Sundar Shrestha (Journal of Nepal Medical Association)
Introduction: Volumetric analysis of the paranasal sinuses can help evaluate disease extent, treatment, and sinus surgery outcome. This study aims to determine the baseline volumes of frontal, maxillary, and sphenoid sinuses. Methods: An observational cross-sectional study was conducted in a tertiary care center after obtaining ethical approval (Reference number: 264/2021). Computerized Tomography Scan head or Computerized Tomography Scan nose/Paranasal sinus images of patients across all age groups from January to December 2022 were analyzed. Sinus volumes were calculated using Digital Imaging and Communications in Medicine software. Results: The study included 154 patients, median age was 29 years (IQR: 22.75 - 39.25) and 84 (54.5%) were male. The median volume of the maxillary sinus was 14.30 cm³ (IQR: 10.76 - 18.02), with the right side at 13.82 cm³ (IQR: 10.34 - 17.39) and the left at 14.62 cm³ (IQR:11.11 - 18.75). The median volume of the sphenoid sinus was 4.52 cm³ (IQR:3.02 - 6.03), with the right side at 4.42 cm³ (IQR: 2.61 - 6.84) and the left at 3.95 cm³ (IQR: 2.16 - 6.47). The median volume of the frontal sinus was 2.59 cm³ (IQR:1.42 - 4.59), with the right side at 2.27 cm³ (IQR:0.94 - 4.12) and the left at 3.04 cm³ (IQR:1.22 - 5.04). Conclusions: Male population had larger volumes across all types. The maxillary and frontal sinuses had the largest and smallest volumes respectively.